Probiotics in Poultry - Widodo, Widodo (Springer, 2015)
The main pathogens associated with poultry farming and production are various serotypes of Salmonella enterica, Escherichia coli and Campylobacter jejuni. Those enteric pathogens are the most common causes of diarrhea in the poultry flock in Indonesia. Their spread are due to poor sanitation and drainage as well as improper litter management, which all lead to bacterial infection in birds. Antibiotics have previously been used for many decades by veterinarians and poultry farmers before they were banned in many countries due to concerns with increased antibiotic resistance in pathogens and antibiotic contamination in food. In the search for an alternative to antibiotics in poultry feed, the addition of probiotics is proposed. Among all the probiotics utilized in poultry production, lactic acid bacteria (LAB) are the most commonly used. The addition of LAB replaces enteric pathogens by means of competitive exclusion in the poultry intestinal tract, thereby increasing the intestinal health of poultry. This chapter discusses the increased growth and performance of poultry due to the application of native LAB.